2021
DOI: 10.1097/ico.0000000000002811
|View full text |Cite
|
Sign up to set email alerts
|

Descemet Stripping Automated Endothelial Keratoplasty in Pediatric Age Group: A Decade of Our Experience

Abstract: This study was to report the outcomes of Descemet stripping automated endothelial keratoplasty (DSAEK) in managing corneal endothelial disorders in children less than 14 years of age.Methods: Medical records of 180 DSAEK performed, between 2008 and 2020, on 167 eyes of 111 children who had a visually significant endothelial dysfunction were retrospectively reviewed for the primary etiology of corneal decompensation, time of the onset and duration of cloudiness, preoperative visual acuity, the technique of endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Although PK has been the technique most widely used to treat corneal endothelial failure in pediatric transplantations, 49 recently other techniques such as anterior or posterior lamellar keratoplasties have been used with success 30–37 . In the Corneal Preservation Time Study, 50 eyes that had undergone surgery for glaucoma had a lower 3-year graft success rate after DSAEK (80.1% vs 94.1% for eyes without glaucoma surgery) 50 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although PK has been the technique most widely used to treat corneal endothelial failure in pediatric transplantations, 49 recently other techniques such as anterior or posterior lamellar keratoplasties have been used with success 30–37 . In the Corneal Preservation Time Study, 50 eyes that had undergone surgery for glaucoma had a lower 3-year graft success rate after DSAEK (80.1% vs 94.1% for eyes without glaucoma surgery) 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Although PK has been the technique most widely used to treat corneal endothelial failure in pediatric transplantations, 49 recently other techniques such as anterior or posterior lamellar keratoplasties have been used with success. [30][31][32][33][34][35][36][37] In the Corneal Preservation Time Study, 50 eyes that had undergone surgery for glaucoma had a lower 3year graft success rate after DSAEK (80.1% vs 94.1% for eyes without glaucoma surgery). 50 However, the subgroups with glaucoma surgery alone, those with prior surgery and medication, and those with medication alone were too small to conduct further analyses on different factors that could influence subsequent graft success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 88 , 89 Ramappa et al reported 10-year outcomes of DSAEK in 180 pediatric eyes and found improved and safe outcomes with this technique. 90 …”
Section: Congenital Opacitiesmentioning
confidence: 99%